2018
DOI: 10.1590/0037-8682-0074-2018
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of human visceral leishmaniasis in the urban centers of the lower-middle São Francisco Valley, Brazilian semiarid region

Abstract: Both cities had a high incidence of VL during the studied period. The findings of this study contribute to a better understanding of the behavior of VL during recent years and may help to direct regional disease control measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 23 publications
(24 reference statements)
0
10
0
3
Order By: Relevance
“…In Brazil, where L. infantum is endemic, the epidemiological data have largely shown a male predominance in VL [54, 8388]. In addition, one nationwide study found higher levels of discontinued therapy among male VL patients.…”
Section: Visceral Leishmaniasismentioning
confidence: 99%
“…In Brazil, where L. infantum is endemic, the epidemiological data have largely shown a male predominance in VL [54, 8388]. In addition, one nationwide study found higher levels of discontinued therapy among male VL patients.…”
Section: Visceral Leishmaniasismentioning
confidence: 99%
“…In addition to the urbanization process 13 , it is important to consider the environmental context and climate change in relation to the spread and maintenance of leishmaniasis. Hot and humid climates favor vector proliferation, increasing the risk of transmission, especially in urban areas with population agglomeration 13 .…”
mentioning
confidence: 99%
“…However, operational difficulties in identifying animal reservoirs allow maintenance of the transmission chain 14 . Furthermore, operational difficulties are also observed in the health system, mainly due to the difficulty of access to health services among poorer population groups, who are often at greater risks of neglected diseases, and due to the poor capacity of health services to identify cases of leishmaniasis early in the community and, consequently, to provide adequate management 13,14 .…”
mentioning
confidence: 99%
“…We performed a cross-sectional study aiming to estimate the prevalence of HIV-Leishmania coinfection in HIV-positive outpatients from the municipality of Petrolina, in the state of Pernambuco, Brazil. Petrolina is an VL-endemic area from where most VL cases in the state of Pernambuco are reported [22]. The study was conducted in a public HIV outpatient clinic, which serviced about 600 individuals regularly using HAART at the time of this investigation.…”
Section: Study Design and Samplementioning
confidence: 99%